ANALISIS KESULITAN SISWA PADA MATERI PENGENALAN GEOMETRI DI KELAS 2 SDN 130 PEKANBARU - Fadillah, Annisa; Alim, Jesi Alexander; Antosa, Zairul (Jurusan Ilmu Pendidikan Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2022)
This study aims to determine the difficulties of students in the introduction of geometry material for grade 2 elementary school students. The research method used in this research is descriptive quantitative method. The data collection technique used is a test technique. The data analysis technique used in this research is descriptive analysis technique and Rasch model analysis. The ability of students to answer questions is very high and it also shows that children's knowledge of geometry is very good. Among the difficulties in learning geometry that often occur in children are lack of understanding of mathematical language, difficulty understanding initial concepts in flat shapes and shapes, difficulties in visual perception and difficulty in distinguishing geometric shapes.